On the analysis of La0.7Ca0.3MnO3 samples using A-C susceptibility - Olarte T., Javier A.; Cifuentes, M.C. (Visión electrónica, 2014)
La0.7Ca0.3MnO3 bulk samples were prepared using solid state reaction methods. The samples were characterized through A.C-Susceptibility and Electron spin resonance (EPR) measurements. A.C-Susceptibility shows a somewhat pronounced single-peak structure in both the real and imaginary part of the susceptibility. Both susceptibility components become mostly frequency independent. The position of the maximum value, however, is slightly shifted by frequency within the experimental resolution. On the other hand, a change from an asymmetrical regime, below Curie temperature (Tc), to a more symmetrical regime above Tc was observed in EPR measurements.